A Case–Control Study of ADCY9 Gene Polymorphisms and the Risk of Hepatocellular Carcinoma in the Chinese Han Population - Chao, Xu; Jia, Yong; Feng, Xuesong; Wang, Guoquan; Wang, Xiaoping; Shi, Hailong; Zhao, Fei; Jiang, Chao (Frontiers in Oncology, 2020)
Background: Adenylyl cyclase type 9 (ADCY9) modulates signal transduction by producing the second messenger cyclic AMP. It has been reported that ADCY9 polymorphisms were associated with cancer development. The aim of this study was to investigate whether ADCY9 polymorphisms could contribute to the susceptibility of hepatocellular carcinoma (HCC) in Chinese. Methods: In the present study, five single nucleotide polymorphisms (SNPs) in ADCY9 were genotyped using Agena MassARRAY platform in 876 subjects from China. Logistic regression was used to assess the effects of SNPs on HCC risk. Associations were also evaluated for HCC risk stratified by age and gender. Results: After adjustment by age and gender, we found a significant relation between heterozygous genotypes of rs2531995 and HCC risk (OR = 1.34, 95% CI = 1.01-1.77, p = 0.045). The individuals with the rs2230742 “AG”, “AA-AG” genotypes underwent a lower risk of HCC (p < 0.05). And, the allelic test showed rs2230742 was associated with an decreased HCC risk (p = 0.006). Further stratified analysis showed that rs879620 increased HCC risk and rs2230742 was associated with lower HCC risk in the individuals aged 55 or younger, rs2531992 significantly decreased HCC risk in the elder group (age > 55). For women, rs2230742 and rs2230741 was significantly associated with HCC risk in multiple models (p < 0.05). In addition, haplotype analysis indicated that Crs879620Ars2230742Ars2230741 haplotype was a protective factor for HCC (OR = 0.67, 95% CI = 0.50-0.88, p = 0.007). Conclusion: Our findings suggest that ADCY9 polymorphisms are associated with HCC risk in Chinese Han population.